Od kapliczki do mody. Obraz Maryi w kulturze współczesnej - Andrzej Draguła (Colloquia Theologica Ottoniana, 2018)
In Catholicism, Our Lady’s role among the saints is special, as she is the mother of Jesus, Son of God. Her uniqueness is reflected also in the culture stemming from Christianity. Here she constitutes the prototype of womanhood, maternity and mother-figure combining the cult of Our Lady and the relics of the pre-Christian cult of mother goddess. In popular piety, and especially in its rural version, the figure of Our Lady appeares in two ways: as Mary of Nazareth, known from the pages of the Gospel, and as the coming from heaven Mother of God. In both cases she is the one who lives with people, sharing their life concerns. Along with urbanization, this cultural model was transferred to the city, as it is shown in the novels of Sylwia Chutnik and Salcia Hałas. The contemporary cultural image of Mary often goes beyond theological orthodoxy, as it can be seen in Ada Karczmarczyk’s “evangelization” attempts, as well as in the use of Mary’s image in art, pop-culture and fashion. The examples presented in the paper indicate that Mary as a character still plays an important part in the contemporary culture, although the way she functions in it is often inconsistent with her image in the Gospel and theology.